Optimization of glutaraldehyde concentration in relation to swelling behavior of PVA-PEG-BTB film using hybrid genetic metaheuristic algorithm - Daeuk Kim; Izabelle Nisha Maxine D. Chan; Tosha Mae S. Manalastas; Ronnie S. Concepcion II; Joseph Rey H. Sta. Agueda; Rafael Kyle B. Bitangcor (Scientific Reports)
Abstract The crosslinking characteristics of hydrogels and polymeric films critically influence their swelling capacity, a key factor in wound care applications. This study optimized the swelling behavior of polyvinyl alcohol (PVA)–polyethylene glycol (PEG)–bromothymol blue (BTB) films using three hybrid metaheuristic algorithms: Hybrid Genetic-Hippopotamus Optimizer (HG-HO), Hybrid Genetic-Walrus Optimization Algorithm (HG-WOA), and Hybrid Genetic-Horned Lizard Optimization Algorithm (HG-HLOA). Among these, HG-HLOA achieved the fastest convergence, while all algorithms reliably identified optimal solutions with comparable fitness values. The optimal glutaraldehyde concentration was determined as 4.9251 wt%, with a predicted maximum swelling ratio of 1217.7311%. Experimental validation yielded an average swelling ratio of 1225.7123%, differing by only 0.65% from the predicted value. An increasing trend in swelling ratio was observed with rising glutaraldehyde concentration up to the optimum point, followed by a decrease due to possible over-crosslinking and formation of acetal linkages. This trend was supported by structural analysis using Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron Microscopy (SEM). Statistical analysis via Analysis of Variance (ANOVA) confirmed a significant relationship between glutaraldehyde concentration and swelling ratio, with a p-value of 2.1e−161.